Indeterminate Thyroid Nodules: A Pragmatic Approach. Issue 1 (21st January 2018) - Khalil, Aly Bernard; Dina, Roberto; Meeran, Karim; Bakir, Ali M.; Naqvi, Saf; Al Tikritti, Alia; Lessan, Nader; Barakat, Maha T.
Abstract : Background: Fine needle aspiration (FNA) cytology fails to provide a conclusive diagnosis in a subset of thyroid lesions labeled as "indeterminate" (Thy3). In this study, we aimed at ascertaining the prevalence of Thy3 thyroid nodules in a hitherto unreported ethnic group (residents of the United Arab Emirates). Methods: We retrospectively examined 688 FNA of the thyroid performed on 584 patients. Samples were reported using the Royal College of Physicians' (RCP) Thy classification. The results of the FNA were correlated with the final surgical specimens. Ultrasonography (US) risk stratification was calculated using a web-based US risk of malignancy calculator. Results: Overall sample adequacy was 97%. The indeterminate group Thy3 was found in 7% of the samples. The overall risk of malignancy in the Thy3 category was 20%. This risk was very similar in the 2 subgroups of Thy3 (17% in Thy 3a and 22% in Thy3f). Subdividing the Thy3 group into subgroups becomes less necessary if the US scoring is <24.5% since the negative predictive value, in this case, is 100%. Applying this criterion to our population would have had the potential of reducing the percentage of patients referred to surgery from 61 to 43%. Conclusions: Proper risk stratification of Thy3 lesions should be based on the combined risk assessment of clinical, cytological, radiological, and molecular data. Such a pragmatic approach is expected to reduce the percentage of inappropriate referrals to surgery.